2000
DOI: 10.1046/j.1365-2516.2000.00355.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect kinetics of desmopressin‐induced platelet retention in healthy volunteers treated with aspirin or placebo

Abstract: Desmopressin is often used for haemostatic treatment in platelet dysfunction, but the effect kinetics of platelet responses and the mechanism of action are poorly known. This study aimed to determine the kinetics of platelet function responses induced by desmopressin in healthy volunteers treated with aspirin or placebo. Another aim was to correlate platelet responses to changes of von Willebrand factor (vWF) in plasma. We measured platelet function with a glass bead retention test, Ivy bleeding time, vWF:Ag a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 24 publications
2
10
0
4
Order By: Relevance
“…There was no significant difference for desmopressin in the ED 50 values induced by collagen, compared with either NXY‐059 or placebo. Desmopressin significantly increased platelet adhesion compared with placebo and NXY‐059, which was expected, based on published observations 18 …”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…There was no significant difference for desmopressin in the ED 50 values induced by collagen, compared with either NXY‐059 or placebo. Desmopressin significantly increased platelet adhesion compared with placebo and NXY‐059, which was expected, based on published observations 18 …”
Section: Discussionsupporting
confidence: 79%
“…With 30 subjects, the power of a 1‐sided level of 10% t test in the appropriate linear model to detect the 35% reduction in bleeding time (desmopressin compared with placebo) reported by Lethagen et al 18 is at least 90%.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Mannucci showed that DDAVP has no direct effect on platelet count or aggregation, but enhances platelet adhesion to the vessel wall [1]. Lethagen et al [24] also showed that the effect of DDAVP on platelet adhesion may not be secondary to the vWF increase. It has been known that another relevant mechanism that accounts for the haemostatic effect of DDAVP is mediated by the release of high-molecular-weight multimers of vWF in endothelial cells [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…This effect lasts approximately 3 hours, although the platelets can be stimulated again. The effect on platelet adhesion seems to be independent of the increase in the plasma vWF levels [10]. Desmopressin also shortens the activated partial thromboplastin time (APTT) and the bleeding time [11].…”
Section: Desmopressinmentioning
confidence: 99%